Data from: Interspecific analysis of vehicle avoidance behavior in birds - Husby, Arild; Husby, Magne (Zenodo, 2014)
Among the most widespread forms of anthropogenic modification of the natural landscape is road construction, with vehicle mortality a major issue affecting amphibians, reptiles, mammals, and birds. Why some species are more susceptible to vehicle collision than others, however, is poorly understood. We examine how roadside vegetation patterns, road size, vehicle speed, and brain size influence vehicle avoidance behavior using more than 3700 individuals of 11 species of European birds. We find that on larger roads and at higher vehicle speeds, birds were more likely to fly away from the road than to cross it. Moreover, species with a larger relative brain size flew away from the road more often than species with a small brain size, something that may in part explain interspecies differences in vehicle collision mortality rates. Our results provide important insights into factors that influence vehicle avoidance behavior in birds and show that brain size can be an important trait for adjusting to novelties in their environment. Datafile Datafile. See Readme file for further description. dryaddata.csv